PENGARUH INSULIN TERHADAP FUNGSI KARDIOVASKULAR - Ridwan, Muhammad; Gotera, Wira (journal of internal medicine, 2012)
Insulin is an anabolic hormone responsible for regulation of glucose metabolism and signals for storage and usage of many fundamental nutrients such as glucose, amino acids, and fatty acids. Its effects on cardiovascular function, reveal wider early-known insulin actions, are based on the balance between its NO-dependent vasodilator action and endothelin-1-dependent vasocontriction action regulated by signals through phosphatidylinositole 3-kinase (PI3K) and mitogen-activated protein kinase (MAPK)-dependent pathways on vascular endothelial cells. On insulin resistance setting, signal perturbances of PI3K pathway and enhanced signals through MAPK pathway are conditions underlying link between metabolic disorders and cardiovascular diseases. Insulin also has antiinflammatory effects by suppressing expression of ICAM-1, MCP-1, NF-kB, MMP-9 and CRP. On the heart, insulin increases contractility and plays important roles in maximazing heart glucose uptake particularly in stress states. In addition, insulin plays a role in physiologic heart growth through Akt pathway. However, chronic exposure of insulin is associated with ventricular disfunction. In term of cardiovascular function, insulin is known to increase peripheral blood flow dan to decrease peripheral resistance, so that results in enhanced cardiac output without significant changes in blood pressure. Not only can improved insulin action repair glucose metabolism, but also improve risks underlying atherosclerosis and cardiovascular complications of diabetes. In 2007, European Cardiac Society (ESC) has recommended intensive insulin usage to tightly control blood glucose in order to improve adult critically ill and heart surgery patient mortality and morbidity
Keywords: insulin, cardiovascular, nitric oxide